Anion‐Regulated Selective Generation of Cobalt Sites in Carbon: Toward Superior Bifunctional Electrocatalysis. Issue 47 (6th November 2017) - Wan, Gang; Yang, Ce; Zhao, Wanpeng; Li, Qianru; Wang, Ning; Li, Tao; Zhou, Hua; Chen, Hangrong; Shi, Jianlin
Abstract: The introduction of active transition metal sites (TMSs) in carbon enables the synthesis of noble‐metal‐free electrocatalysts for clean energy conversion applications; however, there are often multiple existing forms of TMSs, which are of different natures and catalytic models. Regulating the evolution of distinctive TMSs is highly desirable but remains challenging to date. Anions, as essential elements involved in the synthesis, have been totally neglected previously in the construction of TMSs. Herein, the effects of anions on the creation of different types of TMSs are investigated for the first time. It is found that the active cobalt–nitrogen sites tend to be selectively constructed on the surface of N‐doped carbon by using chloride, while metallic cobalt nanoparticles encased in protective graphite layers are the dominant forms of cobalt species with nitrate ions. The obtained catalysts demonstrate cobalt‐sites‐dependent activity for oxygen reduction reaction and hydrogen evolution reaction in acidic media. The remarkably enhanced catalytic activities approaching that of benchmark Pt/C in an acidic medium have been obtained on the catalyst dominated with cobalt–nitrogen sites, confirmed by the advanced spectroscopic characterization. This finding demonstrates a general paradigm of anion‐regulated evolution of distinctive TMSs, providing a new pathway for enhancing performances of various targeted reactions related with TMSs. Abstract : A versatile anion‐regulated selectivity generation strategy of transition metal sites (TMSs) is successfully demonstrated via exploring the neglected importance of anions involved in the synthesis. The controlled evolution of cobalt–nitrogen coordination sites on the surface of cobalt nanoparticles within the protective graphite layers in N‐doped carbon is achieved, which demonstrates cobalt‐site‐dependent hydrogen evolution reaction (HER) and oxygen reduction reaction (ORR) catalytic performances in acidic media.